Human CD34+-derived plasmacytoid dendritic cells as surrogates for primary pDCs and potential cancer immunotherapy - Fiore, Giovanna; Weckwarth, Wolfgang; Paetzold, Kerstin; Albertí Servera, Llucia; Gies, Manuela; Rosenhauer, Jakob; Antoniolli, Martina; Nassiri, Sina; Schmeing, Stephan; Dettling, Steffen; Soni, Bhavesh; Majety, Meher; et al. (Frontiers in Immunology, 2024)
Introduction Plasmacytoid dendritic cells (pDCs) are capable of triggering broad immune responses, yet, their scarcity in blood coupled to their reduced functionality in cancer, makes their therapeutic use for in situ activation or vaccination challenging. Methods We designed an in vitro differentiation protocol tailored for human pDCs from cord blood (CB) hematopoietic stem cells (HSCs) with StemRegenin 1 (SR-1) and GM-CSF supplementation. Next, we evaluated the identity and function of CB-pDCs compared to human primary pDCs. Furthermore, we tested the potential of CB-pDCs to support anti-tumor immune responses in co-culture with tumor explants from CRC patients. Results Here, we report an in vitro differentiation protocol enabling the generation of 200 pDCs per HSC and highlight the role of GM-CSF and SR-1 in CB-pDC differentiation and function. CB-pDCs exhibited a robust resemblance to primary pDCs phenotypically and functionally. Transcriptomic analysis confirmed strong homology at both, baseline and upon TLR9 or TLR7 stimulation. Further, we could confirm the potential of CB-pDCs to promote inflammation in the tumor microenvironment by eliciting cytokines associated with NK and T cell recruitment and function upon TLR7 stimulation ex vivo in patient tumor explants. Discussion This study highlights CB-pDCs as surrogates for primary pDCs to investigate their biology and for their potential use as cell therapy in cancer.